Broken symmetry phase transition in solid HD: a manifestation of quantum orientational melting - Freiman, Yu. A.; Tretyak, S. M.; Jezowski, A.; Hemley, R. J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
Theoretical study of the broken symmetry phase (BSP) transition line in solid HD reveals that its anomalous features provide evidence for quantum orientational melting. The observations of unusual reentrant behavior is a consequence of the symmetry properties of the system, namely, the fact that in HD all rotational states and transitions between them are allowed, in contrast to the behavior of the homonuclear isotopes H2 and D2. The systematic underestimation of the transition pressure characteristic of all theories of the BSP transition can be removed if crystal-field effects are taken into account.